Pengaruh Profitabilitas, Solvabilitas, Likuiditas, Ukuran Perusahaan Dan Opini Audit Terhadap Audit Delay - Rusminah, Rusminah; Nursanty, Ida Ayu; Amrul, Rusli; Prathama, Baiq Desthania; Kartini, Endang; Octavia, Yusi Faizatul (Akuntansi & Ekonomika, 2023)
This research aims to investigate the influence of profitability, solvency, liquidity, company size, and audit opinion on audit delay in Property and Real Estate companies. The study employs a quantitative approach with purposive sampling, involving 23 companies in the sample. Data analysis is conducted through multiple linear regression. The results indicate that profitability does not have a significant effect on audit delay. However, debt payment and company size significantly influence audit delay. While liquidity, though not significant, does affect audit delay. Auditor opinion also significantly influences audit delay. These findings provide valuable insights for stakeholders such as company management, auditors, and regulators in understanding the factors influencing audit delay in the Property and Real Estate sector.